THE EFFECTIVENESS OF USING COMIC IN TEACHING READING TO THE SECOND GRADERS OF JUNIOR HIGH SCHOOL - Mirasari, Novita Putri; Basuni, Muh. (Lingua Scientia, 2016)
Reading is important skill to help people learn from human knowledgeand experience. Through reading, knowledge has greatly contributedto the growth of mankind. Reading, in particular, helps languagelearners obtain a lot of knowledge by actively and critically relate theideas of the text. Nevertheless, it is not easy to read for comprehension.This study is intended to measure the effectiveness of using comic inteaching reading to the second graders of Junior High School. Theresearch design was pre-experimental one group pretest post test.Thepopulation of this study was all student of are all of second gradestudents at SMPN 1 Sumbergempol.The sample was VIII E classconsisting of 27 students.The research instruments was a test. Thedata analysis was using T test. The result showed that the studentsâmean score in teaching reading before treatment just only 67.48. Whilethe studentsâ score after treatment was 84.52. At the signifcance levelof 0.05, the score of t table is 2.056. By comparing the âtâ that theresearcher has got calculation t count (8.625) and the value of âtâ onthe t-table tt = 0.05 (2.056). It is known that t-count is bigger thant-table = (8.625 > 2.056).Because the tcount is bigger than ttable thealternative hypothesis (Ha) is accepted and the null hypothesis (Ho)is rejected, it means that there is different reading mean score of thesecond grade at SMPN 1 Sumbergempol between before being taughtby using comic and after taught by using comic. It can be concluded that using comic in teaching reading is effective.